The Effect of the Discovery Learning Model through the Aptitude Treatment Interaction (ATI) on Student Learning Outcomes on the Human Motion System Concept - Widyastuti, Lina; Usman, Usman; Rifqiawati, Ika (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
This study aimed to determine the effect of the Discovery Learning model through the Aptitude Treatment Interaction on students' cognitive abilities in the concept of the human motion system. The method used in this research is quasi-experimental with a pretest-posttest control group design. The population in this research is all students in grade XI MIPA SMAN A Serang City in the 2021/2022 academic year. The sample of this research is class XI MIPA 1 as the experimental class and class XI MIPA 2 as the control class. The sampling technique used in this research was purposive sampling. Data collection technique used posttest to measure student cognitive abilities taken at the beginning and the end of learning. Learning outcomes showed that the average value of students' cognitive skills in experimental class is 84, an excellent category. In contrast, the average value in the control class produces a score of 74 in the superb category. To prove the hypothesis, the writer counted the significance by using a t-test (t-test) of the Independent Simple T-test, the student's cognitive learning outcomes are 0,002, so it can be concluded that there is an effect of the discovery learning model through the Aptitude Treatment Interaction (ATI) approach on student learning outcomes on the concept of motion systems in humans.